2009
DOI: 10.1007/978-3-642-00768-2_21
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Adaptive State Space Caching Based on Level Sampling

Abstract: Abstract. In the past, several attempts have been made to deal with the state space explosion problem by equipping a depth-first search (DFS) algorithm with a state cache, or by avoiding collision detection, thereby keeping the state hash table at a fixed size. Most of these attempts are tailored specifically for DFS, and are often not guaranteed to terminate and/or to exhaustively visit all the states. In this paper, we propose a general framework of hierarchical caches which can also be used by breadth-first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…We plan to experiment with state space caching techniques [33] and with other on-the-fly reductions to accelerate CTG generation in TESTOR. We also plan to investigate how to facilitate the description of test purposes, by deriving them from the action-based, branching-time temporal properties of the model (following the results of [13] in the state-based, linear-time setting) or by synthesizing them according to behavioral coverage criteria.…”
Section: Resultsmentioning
confidence: 99%
“…We plan to experiment with state space caching techniques [33] and with other on-the-fly reductions to accelerate CTG generation in TESTOR. We also plan to investigate how to facilitate the description of test purposes, by deriving them from the action-based, branching-time temporal properties of the model (following the results of [13] in the state-based, linear-time setting) or by synthesizing them according to behavioral coverage criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that in state space exploration, due to the characteristics of most networks, there is a strong sense of locality, i.e. in each search iteration, the set of new state vectors is relatively small, and most of the already visited vectors have been visited about two iterations earlier [28,36]. This allows effective use of block local state caches in shared memory.…”
Section: Closed Set Maintenancementioning
confidence: 99%
“…Research has shown that in state space exploration, due to the characteristics of most networks, there is a strong sense of locality, i.e. in each search iteration, the set of new state vectors is relatively small, and most of the already visited vectors have been visited about two iterations earlier [18,19]. This allows effective use of block local state caches in shared memory.…”
Section: Closed Set Maintenancementioning
confidence: 99%
“…If the vector is not old, then it is attempted to insert it in the bucket (lines [15][16][17][18][19][20][21][22][23]. This is done by the warp leader (WarpTId = 0, line 18), by performing a CAS.…”
Section: Global Hashmentioning
confidence: 99%